MEDIA PEMBELAJARAN POP UP BOOK DENGAN TEKNIK BOX AND CYLINDER DALAM MENINGKATKAN PRESTASI BELAJAR PADA PEMBELAJARAN IPAS KELAS IV - Rendi Alfian Susanto; Wahyu Kurniawati (STKIP Subang, 2024)
The research on Pop Up Book learning media using the Box and Cylinder technique was motivated by the low achievement of science and science learning in class IV elementary schools. This research and development uses a research model, namely 4D. The study was carried out at SD Negeri Dalangan 1 and SD Negeri Sutan in the Kapanewon Minggir area. By collecting data using interviews, questionnaires and tests. The results of this research resulted in validation from experts and responses from students and teachers. The results of the validation by media experts and IPAS experts obtained the criteria